ANALISA SISTEM INFORMASI PERSEDIAAN MASUK DAN KELUAR BARANG GUDANG PADA CV. CIPTA USAHA NAGARI - Jibrael Yutomo Tunu; Nur Nawaningtyas Pusparini (EBID: Ekonomi Bisnis Digital, 2023)
Any business, whether manufacturing, trading, or providing services, needs to have inventory to do business. A company's production performance is usually stored temporarily before being sent to consumers. So storing goods in a warehouse is very important because it greatly influences customer satisfaction (Olivia Audrey et al., 2019). Service is a type of facility that all businesses offer to keep their customers there. Good service has a positive impact on a business because when consumers are satisfied with the services provided by a business, these consumers will make repeat purchases and consumers can recommend business locations that offer these services (Sihombing, 2020). The methodology in this research is descriptive and qualitative. Descriptive research is the main focus used to investigate a condition, situation, or other event. Qualitative research is a main focus used to understand human or social phenomena through a way of creating or making comprehensive and complex pictures that can also be explained using words and to provide an overview. This research aims to observe the system scheme that runs for the process of entering oil goods at the CV warehouse. Create Nagari Business. Conclusion From the results of observations made by the author, it can be concluded that the activities of receiving and releasing goods and the recording process may not be in harmony because the existing system is not capable of carrying out these activities. This can happen due to several factors such as poor service systems, lack of access to outgoing information, and incoming information, storage of goods, as well as inappropriate physical environmental conditions for the goods being stored.